2020
DOI: 10.1090/proc/14909
|View full text |Cite
|
Sign up to set email alerts
|

Complex symmetric composition operators on weighted Hardy spaces

Abstract: Let φ \varphi be an analytic self-map of the open unit disk D \mathbb {D} . We study the complex symmetry of composition operators C φ C_\varphi on weighted Hardy spaces induced by a bounded sequence. For any analytic self-map of D \mathbb {D} that is not an elliptic automorphism, we establish that if C φ C_{\varphi } is complex symmetric, then eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…At the beginning, research was mainly focused on the study of complex symmetric operators on abstract Hilbert spaces (see [3][4][5]). As research continued, experts and scholars began to consider some special complex symmetric operators (such as composition operators and weighted composition operators) on analytic function spaces (see [6][7][8][9][10][11][12][13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning, research was mainly focused on the study of complex symmetric operators on abstract Hilbert spaces (see [3][4][5]). As research continued, experts and scholars began to consider some special complex symmetric operators (such as composition operators and weighted composition operators) on analytic function spaces (see [6][7][8][9][10][11][12][13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, complex symmetric composition operators and weighted composition operators acting on some Hilbert spaces of analytic functions have been studied considerably. See [3][4][5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]28] for more results on complex symmetric operators.…”
Section: Introductionmentioning
confidence: 99%
“…In [28, Theorem 2.5], Narayan, Sievewright and Tjani have shown that if Φ is an analytic self-map of U which is not an elliptic automorphism and C Φ is complex symmetric on H 2 (U), then Φ(0) = 0 or Φ is linear. They also characterized the non-automorphic linear self-maps of U that induce complex symmetric composition operators (see [28,Theorem 3.1]). In [29], Noor and Severiano characterized all linear fractional self-maps Φ of C + that induce complex symmetric composition operators C Φ on H 2 (C + ).…”
Section: Introductionmentioning
confidence: 99%